1991
DOI: 10.1016/0042-6822(91)90795-d
|View full text |Cite
|
Sign up to set email alerts
|

Random nature of coronavirus RNA recombination in the absence of selection pressure

Abstract: RNA-RNA recombination is thought to occur preferentially at certain selected sites and in only a few RNA viruses; the mechanism for these restrictions is unknown. In this paper we report the development of a recombination assay for coronavirus, using polymerase chain reaction, in the absence of selection pressure. Our results showed that within a 1-kb region of the peplomer gene, RNA recombination occurred at almost every potential crossover site. Thus, coronavirus RNA recombination appears to be more random t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
106
0
3

Year Published

1992
1992
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(113 citation statements)
references
References 20 publications
4
106
0
3
Order By: Relevance
“…For example, previous studies have identified a recombinational hot-spot region in mouse hepatitis coronavirus (Banner et al, 1990). However, in the absence of selection, initial recombination events were randomly distributed, but after several passages of the recombinant viruses in tissue culture, recombination sites became localized to a restricted region corresponding to the initially identified hot spot (Banner & Lai, 1991). This study suggests that RNA recombination is more frequent than previously thought, and also that the recombinant viruses obtained may reflect the results of selective pressure rather than the mechanism of recombination itself.…”
Section: Recombination In Rna Virusesmentioning
confidence: 99%
“…For example, previous studies have identified a recombinational hot-spot region in mouse hepatitis coronavirus (Banner et al, 1990). However, in the absence of selection, initial recombination events were randomly distributed, but after several passages of the recombinant viruses in tissue culture, recombination sites became localized to a restricted region corresponding to the initially identified hot spot (Banner & Lai, 1991). This study suggests that RNA recombination is more frequent than previously thought, and also that the recombinant viruses obtained may reflect the results of selective pressure rather than the mechanism of recombination itself.…”
Section: Recombination In Rna Virusesmentioning
confidence: 99%
“…Putative leader-body junction sites have also been identified on the genomes of LV (Meulenberg et al, 1993) and LDV (Kuo et al, 1992). Arterivirus replication is similar to that of coronaviruses (de Vries et al, 1990;den Boon et al, 1991) during which RNA recombination, unusual amongst RNA viruses, has been reported to occur (Banner et al, 1990;Banner & Lai, 1991;Keck et al, 1988;Lai et al, 1985;Makino et al, 1986;Wang et al, 1993).…”
mentioning
confidence: 89%
“…The data provide statistical evidence for intragenic recombination in ORFs 2, 3, 4, 5 and 7, but not ORF 6 ( Table 2). The apparent lack of recombination in ORF 6 may be due to selection against recombinant forms, as described in coronaviruses (Banner & Lai, 1991 …”
Section: Intragenic Recombination In Prrs Virus Genesmentioning
confidence: 99%